14-3-3σ induces heat shock protein 70 expression in hepatocellular carcinoma - Liu, Chia-Chia (BioMed Central, 2014)
BACKGROUND: 14-3-3σ is implicated in promoting tumor development of various malignancies. However, the clinical relevance of 14-3-3σ in hepatocellular carcinoma (HCC) tumor progression and modulation and pathway elucidation remain unclear. METHODS: We investigated 14-3-3σ expression in 109 HCC tissues by immunohistochemistry. Overexpression and knockdown experiments were performed by transfection with cDNA or siRNA. Protein expression and cell migration were determined by Western blot and Boyden chamber assay. RESULTS: In this study, we found that 14-3-3σ is abundantly expressed in HCC tumors. Stable or transient overexpression of 14-3-3σ induces the expression of heat shock factor-1α (HSF-1α) and heat shock protein 70 (HSP70) in HCC cells. Moreover, expression of 14-3-3σ significantly correlates with HSF-1α/HSP70 in HCC tumors and both 14-3-3σ and HSP70 overexpression are associated with micro-vascular thrombi in HCC patients, suggesting that 14-3-3σ/HSP70 expression is potentially involved in cell migration/invasion. Results of an in vitro migration assay indicate that 14-3-3σ promotes cell migration and that 14-3-3σ-induced cell migration is impaired by siRNA knockdown of HSP70. Finally, 14-3-3σ-induced HSF-1α/HSP70 expression is abolished by the knockdown of β-catenin or activation of GSK-3β. CONCLUSIONS: Our findings indicate that 14-3-3σ participates in promoting HCC cell migration and tumor development via β-catenin/HSF-1α/HSP70 pathway regulation. Thus, 14-3-3σ alone or combined with HSP70 are potential prognostic biomarkers for HCC.